STRATEGI PEMBELAJARAN BAGI ANAK BERKEBUTUHAN KHUSUS DI SLB - Oki Dermawan (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2013)
Special need children is used to replace extraordinary children indicating specific abnormalities had. Special need children have different characteristics from one another. The characteristics and constraints had make them require special education services adapted with their abilities and potential. Special need children have physical, emotional, mental, intellectual, or or social weakness and strength. Proposing expansion and equalization of educational services for special need children in SLB PKK Bandar Lampung, school should be pro-active in socializing the existence of special education.